The fish fauna of the Argentine islands region (Antarctica; 12 UAE 2007-2008) and morphometrical changeability of Notothenia coriiceps (Richardson, 1844) - Trokhymets, V. M.; Tymofyeyev, V. A.; Perechrest, J. S. (Ukrainian Antarctic Journal, 2010)
Information deals with specific composition of fish species which was marked during wintering 2007-2008 near the Ukrainian Antarctic Station Akademik Vernadsky (Argentina’s archipelago, Antarctic Region). The quantitative indexes of fishes of different species are explored and the analysis of their dominant groups is conducted. It is found out that in 2007-2008 happened subdominant changes in comparison with previous years of researches. So, if in the previous years Trematomus bernacchii was subdominant during our researches the representatives of Notothenia rosii prevailed already. Biological and morph-metrical comparative analyses of two groups Notothenia coriiceps from the district of channel of Meek-Penola and near-by the bank of the west of island of Grotto were conducted. It is exposed, that these two groups of fish species divided, probably, on the different herds. Somatic indexes did not show considerable changeability, except for hepatosomatic, but individuals of both groups of fish species had the low indexes of adiposeness and fatness.